Relaciones de comedia en Cerdeña: los pliegos del taller sevillano de los Hermosilla (1684-1739) en la Biblioteca Universitaria de Cagliari - Gabriel Andrés (Janus: Estudios sobre el Siglo de Oro)
This paper provides a bibliographical study on eighteen texts of “relaciones de comedia” preserved in the University Library of Cagliari (Sardinia) and produced by Hermosilla Printing office at Seville between 1685-1738. It includes a bibliographical repertory of thouse broadsheets or “pliegos sueltos” at the begnining of the 18th century and the edition of two unknown pieces.